ASSESSMENT OF PROFESSIONAL COMPETENCE OF SPECIALISTS TRAINED FOR THE NATIONAL ECONOMY OF THE RUSSIAN FEDERATION - E. L. Kruglova (Вестник университета)
The article describes and analyses the results of the monitoring carried out following the results of the training of specialists trained for organizations of the national economy of the Russian Federation in accordance with the state plan for the training of management personnel. The data of the last monitoring of the 2019/2020 academic years were compared with the results of previous years using general scientific and specific sociological methods. Based on the results of the analysis, the author proposes changes and innovations in the methodology for assessing the professional competence of the graduates of the Program. The assessment methodology has a clear structure, stages, uses mathematical tools to calculate the level of competence in order to exclude subjectivity in the analysis.